Comparative acaricidal efficacy of the topically applied combinations fipronil/(S)-methoprene, permethrin/imidacloprid and metaflumizone/ amitraz against Dermacentor reticulatus, the European dog tick (ornate dog tick, Fabricius, 1794) in dogs* - Tielemans E.; Manavella C.; Polmeier M.; Chester T.; Murphy M.; Gale B. (Parasite, 2010)
The acaricidal efficacy against Dermacentor reticulatus in dogs of the commercial topical combinations fipronil/(S)-methoprene (FRONTLINE Combo® spot-on dog), imidacloprid/permethrin (Advantix®) and metaflumizone/amitraz (ProMeris Duo®) was evaluated and compared. Three treatment groups and one untreated control group of six adult Beagle dogs each were randomly formed. Each treatment was administered topically once on Day-0, according to the recommended label dose and instructions for use. All dogs were infested weekly with approximately 50 adult unfed D. reticulatus over a period of seven weeks. Ticks were removed and counted approximately 48 hours after each infestation. The percent reduction in numbers of ticks for fipronil/(S)-methoprene was ≥ 97 % compared to untreated controls for all seven weekly infestations. The percent reductions for imidacloprid/permethrin and metaflumizone/amitraz were satisfactory initially but fell and stayed below 90 % after three weeks. From the third week onwards, fipronil/(S)-methoprene treated dogs had significantly fewer ticks than imidacloprid/ permethrin or metaflumizone/amitraz treated dogs (p < 0.05).